Pemberian Upah Dalam Praktik Bekam (Al-Hijamah) - Nst, Rusli Halil (-, 2024)
Abstract: Cupping therapy, also known as hijamah, is a traditional medical practice that involves drawing out impure blood from the body for detoxification and healing purposes. This study aims to analyze the differing opinions among Islamic scholars regarding the permissibility of charging a fee for cupping therapy. The qualitative research approach was employed, utilizing content analysis of classical and contemporary literature, as well as interviews with cupping practitioners and religious figures in Balik Pulau, Penang Island. The findings of the study reveal that cupping therapy has been practiced since the time of Prophet Lot and is recognized in various ancient medical traditions, including Islam. According to Islamic law, cupping therapy is encouraged and permitted. However, there are varying opinions regarding the acceptance of fees. Some scholars prohibit it, while others allow it under certain conditions. The interviews conducted indicate that cupping therapy is effective and well-received by the community, with a majority approving of charging a fee due to its benefits in ensuring adequate facilities. In conclusion, the study determines that charging a fee for cupping therapy is permissible as long as it does not burden the patient and adheres to Shariah principles. Additionally, the importance of providing proper facilities for this practice is emphasized.Abstrak: Praktik bekam atau hijamah adalah metode pengobatan tradisional yang melibatkan pengeluaran darah kotor dari tubuh untuk detoksifikasi dan penyembuhan. Penelitian ini bertujuan untuk menganalisis perbedaan pendapat ulama terkait pemberian upah dalam praktik bekam. Metode yang digunakan adalah pendekatan kualitatif dengan analisis konten terhadap literatur klasik dan kontemporer, serta wawancara dengan praktisi bekam dan tokoh agama di Balik Pulau, Pulau Pinang. Temuan penelitian menunjukkan bahwa bekam telah lama dipraktikkan sejak zaman Nabi Luth dan diakui dalam berbagai tradisi pengobatan kuno, termasuk dalam Islam. Berdasarkan hukum Islam, praktik bekam dianjurkan dan diperbolehkan. Namun, terdapat perbedaan pendapat mengenai pengambilan upah. Beberapa ulama melarangnya, sementara lainnya memperbolehkan dengan syarat tertentu. Wawancara menunjukkan bahwa praktik bekam efektif dan diterima oleh masyarakat, dengan sebagian besar menyetujui pemberian upah karena manfaatnya dalam penyediaan fasilitas yang layak. Kesimpulan penelitian ini adalah bahwa pemberian upah dalam praktik bekam diperbolehkan selama tidak memberatkan pasien dan sesuai dengan prinsip-prinsip Syariah, serta pentingnya penyediaan fasilitas yang baik dalam praktik ini.